THE BRAIN ROT IN THE AGE OF INFORMATION OVERLOAD: ARE STUDENTS LEARNING LESS BY KNOWING MORE? (Journal of Multidisciplinary Sciences and Innovations, 2025)
In this digital era where information is more accessible than clean air, students are not empowered—they are overwhelmed. This article explores the silent epidemic of information overload and its harmful effects on students’ cognitive capacity. It explores the symptoms of “brain rot,” the unhealthy overreliance on digital technology, and the shift from meaningful understanding to mechanical retrieval. By analyzing academic research, psychological theory, and digital culture, this offers practical strategies educators for implement to foster deeper understanding.